On the Lipschitz stability of inverse nodal problem for p-Laplacian Schrodinger equation with energy dependent potential - Yilmaz, Emrah; Goktas, Sertac; Koyunbakan, Hikmet (Springer International Publishing Ag, 2015)
In this study, we consider reconstruction and stability issues of an inverse nodal problem for a p-Laplacian Schrodinger equation with energy dependent potential. We solve Lipschitz stability of the inverse nodal problem for this p-Laplacian operator. Furthermore, we show that the space of all potential functions q is homeomorphic to the partition set of all asymptotically equivalent nodal sequences induced by an equivalence relation.
Keywords: p-Laplacian operator; inverse nodal problem; Lipschitz stability